A Method for Information Grabbing, Bypassing Security and Detecting Web Application Vulnerabilities - J. Santhosh Kumar, B.; R. Pushpa, B. (International Journal of Engineering and Technology, 2018)
A single file on web contains text, images, audio, video and formatting instructions enclosed within a script. Website files are hosted on servers. The Servers â€œserveâ€ those files to individual users upon request. Anonymous user with minimum user credentials can request on behalf of legitimate user to grab sensitive, confidential and personal information without legitimate users knowledge.[3] The proposed method makes use of URL as input for finding web vulnerabilities. Testing of proposed method is conducted to evaluate the performance based on the accuracy received. Performance is evaluated based on false negative and false positive results. Experiment is also conducted for web vulnerability assessment and penetration testing. The proposed method also checks for information grabbing from web using Google dork. Google dork helps to enter a network without permission and/or gain access to unauthorized information. Advanced searchÂ stringsÂ calledÂ Google dork queries used to locate sensitive information. This paper describes the method for web application vulnerabilities detection by using google dork, bypass first level security in any web and hack username and password in social networking site.Â Â